The Effect of Ethanol Extract of Marsilea crenata Presl. Leaves on Rotenone-Induced Zebrafish Locomotor Activity - Ma'arif, Burhan; Muslikh, Faisal Akhmal; Fihuda, Destiya Argo Pamuji; Khotimah, Husnul; Taek, Maximus M.; Agil, Mangestuti (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2022)
Neurodegenerative diseases are mostly experienced by postmenopausal women and are often caused by estrogen deficiency, so it is necessary to replace the hormone estrogen in the form of phytoestrogens. One of the plants that contain phytoestrogens is Marsilea crenata. The objective of this study is to see if giving rotenone-induced zebrafish a 96% ethanol extract of M. crenata leaves increases locomotor activity. This research was conducted by inducing 5 µg/L rotenone as a compound that will interfere with the locomotor activity of zebrafish. Next, treatment was given with 96% ethanol extract of clover in each group with a dose of 2.5; 5; 10; and 20 mg/mL to determine the effect of the extract on increasing locomotor activity of rotenone-induced zebrafish. Observations were made by looking at the quantity of zebrafish swimming every five minutes until day 28. The treatment of 96% ethanol extract of M. crenata leaves could significantly increase zebrafish motility at the optimum dose of 2.5 mg/mL, because every week the zebrafish locomotor activity increased compared to the negative control. M. crenata leaves extract is proven to prevent neurodegenerative diseases. However, further research needs to be done on the degenerative effects of rotenone every week.